From stubborn resistance is born the State School of Countryside Madre Cristina - Sandra Maria Soares; Ronaldo Eustáquio Feitoza Senra (Universidade Federal do Norte do Tocantins, 2019)
This article presents reflections on the struggles and confrontations experienced by the educators for the continuation of the Madre Cristina-EEMC State School, a school in the countryside. There are also elements to understand the profile of this educator and the formation process, their struggles and experiences in this Settlement. The objectives of this research were: To identify the emergence of the Madre Cristina State School; diagnose the difficulties encountered by the educators in the field in staying in the field; to analyze the process of self-organization of the educators and of the settlers in the struggle for the continuity of the school in the Roseli Nunes-MT settlement. The methodology used was based on the bibliographical research, documentary research of the School's Educational-PPP Project and field research with the application of semi-structured interviews with five EEMC educators and participation in pedagogical meetings, in a qualitative approach, using participant research. The school is the heart of the settlement and being an educator of the countryside is to be oriented to the different dimensions, we verified with this study that the educators of the school have been able to stay in the field, with the support of the settlers and giving continuity to the school in the countryside, nevertheless they experience many challenges in the fight for their stay of the school.